THE USE FGSI AS PREDICTIVE OF UROLOGICAL SIRS PATIENTS - Purnomo, Basuki Bambang (Indonesian Urological Association, 2013)
Objective: To demonstrate the usefulness of Fournier’s Gangrene Severity Index (FGSI) score for differentiating the outcome between Systemic Inflammatory Response Syndrome (SIRS) patients with upper and lower urological abnormalities. Material & Method:A retrospective study of case records from year 2009-2012 of SIRS patients with urological abnormalities at Saiful Anwar General Hospital (SAGH) Malang was carried out. The data were collected from the Medical Record Division in SAGH Malang. SIRS was clinicaly diagnosed based on medical history, physical examination and laboratory findings. SIRS without urological abnormalities were excluded from the analysis. The FGSI, which was developed to assign a numerical score that describes the severity of disease, was used in our study. This index presents patients vital signs (temperature, heart and respiratory rates) and metabolic parameters (sodium, potassium, creatinine, and bicarbonate levels, hematocrit, and white blood cell count). Patients with SIRS and urological abnormalities were divided according to upper tract and lower tract urological abnormalities. Total FGSI score was classified as mild (0-8), moderate (9-17), severe (> 17). The data were assessed according to whether the patient survived or died.Results:75 of the 203 evaluated patients died. From those 75 patients, 67% were male and 33% were female, 75% with upper urological abnormalities and 25% with lower abnormalities (p < 0,05). From those 203 patients; the results were analyzed with binary logistical regression and Spearman correlation analysis using SPSS 15 softwarewith 95% confidence interval (CI). There is significant relationship between FGSI and outcome of the patient with upper urological abnormalities and lower urological abnormalities, with correlation coefficient more high in relationship between FGSI and outcome of the patient with upper urological abnormalities (0,4 vs 0,1). Conclusion: FGSI is simple and objective outcome predictor to differentiate survival between SIRS patients with upper urological abnormalities and lower urological abnormalities. There is a significant difference in outcome between SIRS patient with upper urological abnormalities and lower urological abnormalities even with same level of FGSI score.Keywords: Fournier’s gangrene severity index, systemic inflammatory response syndrome, upper urological abnormalities, lower urological abnormalities, outcome predictor.